The use of acute exercise interventions as priming strategies to improve physical performance during track-and-field competitions: A systematic review - Tan, K.; Kakehata, G.; Lim, J. (Strength and Conditioning Journal, 2024)
The use of exercise interventions to maximize athletes' performance is a common practice in competitions. This systematic review aimed to compile research that explored the effectiveness of priming strategies to maximize physical performance in track and field. The literature search was conducted from PubMed and Scopus. One hundred eighty-two studies were assessed against the inclusion criteria: (a) minimum 1-year participation/competition experience; (b) randomized controlled trials with pre-post intervention outcomes; and (c) studies involving exercise interventions applied =6 hours before outcome measures were collected. Fifteen studies satisfied the criteria and were categorized according to the exercise interventions used (i.e., resistance training, plyometric/ballistic training, resisted sprints, and modified warm-ups). Heavy-loaded resistance training (i.e., >85% 1 repetition maximum) and resisted sprints increased subsequent sprint performance. Plyometrics/ballistic training also positively impacted subsequent jumping (i.e., long jump) and throwing performance (i.e., shot put). Modified warm-ups (i.e., high-intensity sprints and heavier throwing implements) also improved subsequent running and throwing performance. Overall, exercise interventions performed at high intensity and low volume augment subsequent physical performance as close to 4 minutes before the event. However, a sufficient recovery interval must be considered for a positive performance response.